Effects of alloxan on electric activity of mouse pancreatic B cells in vitro - Shen Xin-ming; Su Qing-fen; Qian Zi-wen; Zhang Jing-ru (Acta Pharmacologica Sinica, 2016)
Microelectrode method for recording membrane potentials was used. It was observed that alloxan possessed stimulative and toxic dual effects on the electric activity of pancreatic B cells. A 10-min exposure to alloxan 14 mmol.L-1 in the perfusion medium without glucose caused a significant depolarization of B cells from -44 +/- 13 mV to -36 +/- 12 mV (n = 7, P < 0.05) and evoked spikes in B cells. But the spikes disappeared at 24 +/- 12 min (n = 8). In the presence of glucose 5.5 mmol.L-1 or 11.0 mmol.L-1, the dual effects became weaker or not obvious. After 10-min exposure to diazoxide (an ATP sensitive K+ channel opener) 0.8 mmol.L-1 in the perfusion medium with alloxan 14 mmol.L-1 but devoid of glucose, the amplitude of membrane potential went up from -31 +/- 11 mV to -48 +/- 21 mV and the mean value of spikes dropped from 31 +/- 24 spikes.min-1 to 5 +/- 5 spikes.min-1. It was suggested that the stimulative effect of alloxan was due to blocking of ATP sensitive K+ channel and a higher concentration of glucose could prevent B cells from alloxan injury.